Investigating The Elements That Influencing the Surplus Improvement in Case Where Corporation Size is the Moderating Variable - Petty Aprilia Sari; Purwanti; Suhariyanto (Future Science, 2022)
This research is being conducted to learn more about the impact of Profitability, leverage, and liquidity on the corporation's ability to moderate prices for the subsector manufacturing corporations in Indonesia's Food and Beverages markets (BEI). The 4 years period used for the research period is referred to as the periode 2017-2020. Purposive sampling is the method that is used in sampling. There are 14 businesses based on the criteria that have been established. The kind of data being used is second-level data obtained from the Bursa Efek Indonesia website. Regression data panel analysis is an analytical method used in this study. Data analysis methodology using Eviews 9.0. The findings of this study's uji-T panel indicate that the parsimonious variables Profitability, which is correlated with Return on Equity (ROE), and liquidity, which is correlated with Current Ratio (CR), have a negative impact on the level of laba. However, leverage that is correlated with a low DER (Debt to Equity Ratio) is in influenceive and harmful. In addition to that, the corporation's size is limited to controlling the impact of Profitability as measured by return on equity (ROE) and liquidity as measured by current ratio (CR) on the lab floor. On the other hand, Corporation Size is unable to control leverage that is measured in terms of the Debt to Equity Ratio (DER) in relation to Surplus Improvement.